LE DISCOURS IDENTITAIRE DE L’ENTREPRISE – ÉMOTION, PROMESSES, SÉDUCTION - Andra-Teodora PORUMB (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
The Identity Discourse of the Organization - Emotion, Promises, Seduction. Being the subject of numerous studies carried out by marketing specialists, communication researchers, sociologists and psychologists, the organizational identity is staged with the help of a creative and original discourse, filled with subjectivity and interculturality. We aim to analyse some strategies by which the organization presents its vision, personality and promises by means of its website, especially the particular scenography and isotopes forged in the effort to create a strong image of the brand, gain authority, obtain more credibility, insinuate itself into the memory of the public and select, convince and retain potential customers.